The European Reference Network for Rare Neurological Diseases - Reinhard, Carola; Bachoud-Lévi, Anne-Catherine; Bäumer, Tobias; Bertini, Enrico; Brunelle, Alicia; Buizer, Annemieke I.; Federico, Antonio; Gasser, Thomas; Groeschel, Samuel; Hermanns, Sanja; Klockgether, Thomas; Krägeloh-Mann, Ingeborg; et al. (Frontiers in Neurology, 2021)
While rare diseases are by definition of low prevalence, the total number of patients suffering from a rare disease is high and the majority of them have neurologic manifestations, involving central, peripheral nerve and muscle (1). In 2017, 24 European Reference Networks, each focusing on a specific group of rare or low prevalence complex diseases, were formed to improve the care for patients rare diseases. One major aim is to have “knowledge travel instead of patients”, which has been put into practice by the implementation of the Clinical Patient Management System (CPMS), that enables clinicians to perform pan-European virtual consultations. The European Reference Network for Rare Neurological Diseases, ERN-RND, provides an infrastructure for knowledge sharing and care coordination for patients affected by a rare neurological disease involving the most common central nervous system pathological conditions. It covers the following disease groups: (i) Cerebellar Ataxias & Hereditary Spastic Paraplegias; (ii) Huntington’s disease & Other Choreas; (iii) Frontotemporal dementia; (iv) Dystonia, (non-epileptic) paroxysmal disorders and Neurodegeneration with Brain Iron Accumulation; (v) Leukoencephalopathies; (vi) Atypical Parkinsonian Syndromes. At the moment it unites 32 expert centres and 10 affiliated partners in 21 European countries, as well as patient representatives, but will soon cover nearly all countries of the European Union as a result of the ongoing expansion process. Disease expert groups developed and consented on diagnostic flowcharts and disease scales to assess the different aspects of rare neurological diseases (RND). ERN-RND has started to discuss diagnostically unclear patients in the CPMS, is one of four ERNs that serve as foundation of Solve-RD and has established a RND training and education program. The network will facilitate trial-readiness through the establishment of an ERN-RND registry with a minimal data of all patients seen at the ERN-RND centres, thus, providing a unique overview of existing genotype-based cohorts. The overall aim of the ERNs is to improve access for patients with rare diseases (RDs) to quality diagnosis, care and treatment. Based on this objective, ERNs are monitored by the European Commission on a regular basis to provide transparency and reassurance to the RD community and the general public.